MICRO RAMAN SPECTROSCOPIC ANALYSIS OF LOBULAR CARCINOMA TISSUES - Reveendran, Ambili; Varghese, Sanoj; Kumar V, Senthil; Ranganathan, Venkatesan; Tm, Karthikeyan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: For the past 20 decades, vibrational spectroscopy based studies are undergoing around the world to detect cancer at the earliest stage. Since vibrational spectroscopic techniques have the ability to measure the biochemical changes occur during the time of mutation, which may be the reason for cell proliferation. Biochemical changes may appear in the tissues and blood before the tumor formation. The objective of this work is to study the potential of Raman spectroscopy to detect biochemical changes in the normal and malignant tissues. Methods: In this research work, 10 Raman spectra were acquired from ex vivo samples of human breast tissue (normal and lobular carcinoma) of 10 patients after the removal during prophylactic mastectomy surgery and biopsy. Data analysis was performed using k-means clustering using SPSS and intensity ratio analysis. Result: Intensity variation in the Raman spectra of normal and malignant tissues clearly indicate that Raman spectra are capable to distinguish between normal and malignant tissues. A number of peaks are more in the case of malignant tissues and the presence of amide I and amide III indicate the predominance of protein in malignant tissues. Intensity ratio analysis and K-means clustering analysis also show the significance of protein in lobular carcinoma tissues. Conclusion: This research work proves the potential of Raman spectroscopy to differentiate between the normal breast tissues and lobular carcinoma tissues.